Caffeine Components Empower the Brain Potentiality - Nasim Habibzadeh, Seyedeh (Journal of Spine and Neuroscience, 2020)
The brain requires certain fuels to function in high level. Literally, nutritional components can modulate the brain productivity. One of the right nutrition to enhance the brain power is dietary component of caffeine. Caffeine as a component of coffee, tea and chocolate is very popular. Although, depending on the dietary demands or conventional habits some people do not consume caffeine-containing substances (i.e. foods or beverage). Nonetheless, caffeine constituents maximize the brain potential via promoting the central nervous system (CNS) through blocking an inhibitory neurotransmitter (adenosine) and releasing some other specific neurotransmitters (noradrenaline, dopamine and serotonin) in brain. The chemistry of caffeine in a standard dose in fact can affect the brain intelligence.
Keywords: Caffeine; Brain function; Brain power